A Remark on Perturbed Elliptic Equations of Caffarelli-Kohn-Nirenberg Type - Abdellaoui, Boumediene; Felli, Veronica; Peral, Ireneo (Revista Matemática Complutense, 2005)
Using a perturbation argument based on a finite dimensional reduction, we find positive solutions to the following class of perturbed degenerate elliptic equations with critical growt